2015
DOI: 10.17795/iji-32883
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Joint Infections Due to Coagulase-Negative Staphylococci

Abstract: Context: Staphylococcus aureus and coagulase-negative staphylococci (CoNS) are the most frequently isolated pathogens and are responsible for approximately two-thirds of joint replacement infections. Evidence Acquisition: Although both belong to the staphylococci genus, there are several epidemiological and therapeutic differences between S. aureus and the heterogenous group of CoNS. In general, however, preventive and therapeutic recommendations for Prosthetic Joint Infection PJI due to CoNS do not differ fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…15,17 Contamination lying around the ICU patients was observed in the present study in 95% of the collected samples. For positive Gram, we observed a higher prevalence of bacteria from the group of coagulase-negative Staphylococci -CoNS (76.92%) in relation to the species Staphylococcus aureus (23.07%).…”
Section: Staphylococcus Epidermidissupporting
confidence: 54%
See 2 more Smart Citations
“…15,17 Contamination lying around the ICU patients was observed in the present study in 95% of the collected samples. For positive Gram, we observed a higher prevalence of bacteria from the group of coagulase-negative Staphylococci -CoNS (76.92%) in relation to the species Staphylococcus aureus (23.07%).…”
Section: Staphylococcus Epidermidissupporting
confidence: 54%
“…According to the results from the susceptibility test antimicrobial, 87.5% of the samples identified as CoNS showed resistance to oxacilin, corroborating with previous studies that have estimated that the CoNS isolated in hospitals in Brazil, 70% to 90%, usually have shown resistance to oxacillin. [17][18][19] During the last decades, the substantial increase in CoNS isolated in hospital settings, as well as their oxacillin resistance rates has increased significantly its clinical importance, becoming recognized as opportunistic agents often associated with nosocomial infections. 17,19 As a result, it reinforces the importance of performing increasingly accurate cultures, especially as regards the antibiogram that will contribute to conduct towards the use of more rational way, in a more targeted therapy, particularly in hospital environment.…”
Section: Staphylococcus Epidermidismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar infection rates for all organisms cultured was observed when native joint infections were compared to PJIs, apart from the much higher rates of clinically significant prosthetic infections with CoNS (23.1% vs 4.5% for PJIs and native joint infections respectively, p= <0.001) – this is also in-keeping with other studies carried out in Europe and the US which showed that CoNS together with Staphylococcus aureus are the most common isolated organisms in PJIs, accounting for up to two-thirds of cases. 25 , 26 Higher rates of infection with gram negative organisms was also noted in prosthetic joints (23.1%) compared to native joints (15.9%), but this was not shown to be statistically significant (p= 0.224). It is also interesting to note that no cases of gonococcal arthritis were encountered in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Coagulase-negative staphylococci, with Staphylococcus epidermidis as the most prevalent among all CoNS, are part of the normal microbial flora of human skin. Although these microorganisms are often considered contaminants, deep implant infections caused by those pathogens can lead to severe complications, sometimes even to implant removal [31]. In our study, two deep hip and knee surgical site infections were caused by resistant CoNS.…”
Section: Discussionmentioning
confidence: 60%